ASESMEN YANG EFEKTIF DALAM PERKEMBANGAN BAHASA ANAK USIA DINI - Loka, Novita; Rofiq, Ahmad; Fadilah, Lola; Kalsum, Umi; Apriyani, Nita; Oktafiani, Ilmiah Sholikhah (STKIP Pesisir Selatan, 2025)
Assessment in early childhood education is an assessment process carried out to determine the improvement of children's development. This study focuses on children's language development. This study aims to identify effective assessment methods in measuring the language development of early childhood at RA Al-Fur'qon Prabumulih. This study is a field study with a descriptive qualitative approach. While the data collected through in-depth interviews, participatory observation, and documentation. Not only that, children aged 4-5 years here already understand simple instructions and are able to answer basic questions given by the teacher. In addition, the results of the study also found that the combination of direct observation in daily activities, the use of portfolios, game-based assessments, and parental involvement are the most effective methods at RA Al-Furqon Prabumulih. These methods are considered capable of providing a comprehensive and natural picture of children's language abilities. However, the use of assessment technology is still limited and needs to be improved. While the inhibiting factor is the lack of collaboration between teachers and parents in the field. So that the assessments carried out only apply in schools. This study implies the need for teacher training and integration of digital technology in improving the quality of early childhood assessment.